Percezione del rischio di influenza e attitudine alla vaccinazione degli studenti di medicina e infermieristica durante le campagne vaccinali 2007/2008 (influenza stagionale) e 2009/2010 (influenza H1N1) / Influenza risk perception and vaccination attitude in medical and nursing students during the vaccination campaigns of 2007/2008 (seasonal influenza) and 2009/2010 (H1N1 influenza) - Falato, R.; Riccardi, S.; Franco, G. (La Medicina del Lavoro, 2011)
«Influenza risk perception and vaccination attitude in medical and nursing students during the vaccination campaigns of 2007/2008 (seasonal influenza) and 2009/2010 (H1N1 influenza)». Background: The Italian law on health and safety at work requires that (i) employers provide workers with safe and efficient vaccines, (ii) occupational physicians inform workers about the benefits and inconveniences deriving from immunization. Objective: To assess risk perception of influenza and attitudes to vaccination among medical and nursing students of the School of Medicine of Modena during two vaccination campaigns. Methods: The study, including 598 medical and nursing students (212 vaccinated and 386 non-vaccinated) exposed to influenza virus, was performed in October 2007-April 2008 (during the seasonal influenza campaign), in October-November 2009 and in March-May 2010 (during and after the H1N1 influenza campaign, respectively). Information on influenza risk perception and attitude towards vaccination, as well as perception of different risk factors (smoking, traffic pollution, driving, mobile phones, nuclear power, alcoholic beverages) was collected by a self-administered 4-point Likert scales (1=low risk, 4 high risk) questionnaire. Results: The students perceived the risk of both influenza and of influenza immunization at a lower level compared with other risks. Whereas overall risk perception (excluding influenza and vaccination) was similar within the groups, influenza risk perception was significantly lower in the 2007/2008 group whereas the risk of immunization increased in the 2010 group. Age, gender and being a medical or nursing student did not influence risk perception and vaccination attitude. Conclusion: Although influenza vaccination is recommended, its coverage in medical and nursing students is generally low due to different factors, including underestimation of a preventable disease, lack of knowledge about the benefits of immunization and, according to this study, to the perception of risk associated both with the disease and  immunization practice.